Water Supply and Sanitation Status of Haryzon Polly Dwellers at Natunbazar Area in Mymensingh District (Journal of Environmental Science and Natural Resources, 2016)
Information was collected from various respondents through survey using prescribed questionnaire in Haryzon Polly area at Natun Bazar located under Sadar Upazila in Mymensingh district. It was found that about 56% people were dependent on deep tube-well water for their daily household purpose. The remaining 44% was dependent on tap water supply. According to the respondents, deep tube wells water were mostly used (98%) for drinking purpose and remaining 2% was used by tap water. Of them supply water was used in toilet purpose by 71% and deep tube-well water by 29%. Most of the people of Haryzon Polly at Natunbazar in Mymensingh district were conscious regarding sanitation, but a large portion of them were unaware of safe hygiene. The people dump children feces 60% in open places. Seventeen percentage children did not have any proper knowledge about sanitation. Most of the people have no proper training about sanitation. The survey also indicated that the overall hygienic condition of the respondents and sanitation condition of study area were poor in Haryzon Polly area at Natun Bazar, where both sanitary and hygiene condition were found to be acceptable condition.J. Environ. Sci. & Natural Resources, 9(1): 143-146 2016